Swertianolin ameliorates immune dysfunction in sepsis via blocking the immunosuppressive function of myeloid- derived suppressor cells - Zongfang Ren; Haoren Tang; Linjun Wan; Xing Liu; Ning Tang; Lingling Wang; Zhenhui Guo (European Journal of Histochemistry, 2021)
In this study, we studied the long-term proliferation trajectory of myeloid-derived suppressor cells (MDSCs) in murine sepsis model and investigated whether swertianolin could modulate the immunosuppressive function of MDSCs. A murine sepsis model was established by cecal ligation and perforation (CLP), according to the Minimum Quality Threshold in Pre-Clinical Sepsis Studies (MQTiPSS) guidelines. The bone marrow and spleen of the mice were collected at 24 h, 72 h, 7 and 15 d after sepsis induction. The proportions of monocytic-MDSCs (M-MDSCs; CD11b+LY6G-LY6Chi) and granulocytic-MDSCs (G-MDSC, CD11b+ Ly6G+ Ly6Clow) were analyzed by flow cytometry. Then, we have investigated whether swertianolin could modulate the immunosuppressive function of MDSCs in in vitro experiments. G-MDSCs and M-MDSCs increased acutely after sepsis with high levels sustained over a long period of time. G-MDSCs were the main subtype identified in the murine model of sepsis with polymicrobial peritonitis. Furthermore, it was found that swertianolin reduced significantly interleukin-10 (IL-10), nitric oxide (NO), reactive oxygen species (ROS), and arginase production in MDSCs, while reducing MDSC proliferation and promoting MDSC differentiation into dendritic cells. Swertianolin also improved T-cell activity by blocking the immunosuppressive effect of MDSCs. Both subsets of MDSCs significantly increased in the bone marrow and spleen of the mice with sepsis, with G-MDSCs being the main subtype identified. Swertianolin effectively regulated the functions of MDSCs and reduced immune suppression.